Antidiarrhoeal assessment of hydroalcoholic and hexane extracts of Dracocephalum kotschyi Boiss. and apigenin in mice - Hassan Sadraei; Gholamreza Asghari; Farzaneh Shahverdi (Wolters Kluwer Medknow Publications, 2016)
Dracocephalum kotschyi Boiss, a member of Labiatae family, is a native plant to Iran, which has been reported to have immunomodulatory, antihyperlipidemic and antispasmodic activities. The objective of this research was to study the antispasmodic and antidiarrhoeal activities of hydroalcoholic and hexane extracts of D. kotschyi in mice. Furthermore, the antidiarrhoeal and antispasmodic effect of apigenin, a flavonoid constituent of D. kotschyi, was also studied. Hydroalcoholic and hexane extracts were obtained from aerial part of D. kotschyi using percolation method. Antispasmodic effect of the test compounds was assessed by measurement of small intestine transit following oral administration of a charcoal meal. Diarrhoea was induced by administration of either castor oil (0.5 ml) or magnesium sulphate (MgSO4) (10% w/v solution). Both the hydroalcoholic and hexane extracts of D. kotschyi (10 and 20 mg/kg) reduced the intestinal charcoal meal transit. Loperamide (2 mg/kg) and apigenin (2 and 10 mg/kg) inhibited intestinal movement of the charcoal meal and also inhibited castor oil and MgSO4-induced diarrhoea. The hydroalcoholic and hexane extracts of D. kotschyi (10 and 20 mg/kg) also significantly inhibited the castor oil and MgSO4-induced diarrhoea in mice in comparison with the vehicle-treated control groups. This study confirms that both the hydroalcoholic and hexane extracts of D. kotschyi has antispasmodic and antidiarrhoeal properties in vivo and could be a suitable remedy for treatment of gastrointestinal disorders in which smooth muscle spasm and/or diarrhoea plays a significant roles.